Strength resistance test of superior members for elderly people: comparison between dumbbells with different weights - Marize Amorim Lopes; Giovana Zapellon Mazo; Tânia Rosane Bertoldo Benedetti; Adilson Santana Cardoso; Lucélia Justino Borges; Adriano Ferreti Borgatto (Universidade Federal de Santa Catarina, 2008)
The aim of the study was to compare the performance of elderly people in the strength resistance test of superior members (SRTSM) with dumbbells of different weights (1,8 kg and 2 kg for women and 3,6 kg and 4 kg for men). The sample consisted of 407 elderly (349 feminine and 58 masculine), with age of 60 to 88 years, practitioners of physical exercise for at least six months. The used instrument was the SRTSM of the battery of tests American Alliance for Health, Physical Education, Recreation and Dance (AAHPERD). Two executions of the test were carried through with dumbbells of different weights, SRTSM (1,8 kg and 3,6 kg) and "adjusted" SRTSM (2 kg and 4 kg). For the analysis of the data, it was proceeded descriptive analysis, test t of Student for independent samples, paired t test for dependent samples and ANOVA with post-hoc of Tukey, adopting itself the 5% level significance. The results demonstrated that the use of dumbbells with 4 weights of 2 and kg, seem not to affect the performance of the elderly ones, mainly of the masculine sex. For the feminine sex significant difference in the averages of the second comparison carried through for the sort was detected. However, this difference can have been resulting from external factors to the test, since, the greater average obtained was for "the adjusted" SRTSM. Nevertheless, one tries to facilitate even more the evaluation of the functional capacity of the elderly population, being recommended for SRTSM the use of dumbbells with weight of 2 kg for women and 4kg for men that they are of low cost, easy acquisition and access in the Brazilian market. ResumoO objetivo do estudo foi comparar o desempenho de idosos no teste de resistência de força de membros superiores (RESISFOR) com halteres de diferentes pesos (1,8 kg e 2 kg para mulheres e 3,6 kg e 4 kg para homens). A amostra foi constituída por 407 idosos (349 feminino e 58 masculino), com idade de 60 a 88 anos, praticantes de exercício físico por, no mínimo, seis meses. O instrumento utilizado foi o RESISFOR da bateria de testes American Alliance for Health, Physical Education, Recreation & Dance (AAHPERD). Foram realizadas duas execuções do teste com halteres de pesos diferentes, RESISFOR (1,8 Kg e 3,6 Kg) e RESISFOR "ajustado" (2 Kg e 4 Kg). Para a análise dos dados, procedeu-se a análise descritiva, Teste t de Student para amostras independentes, Teste t pareado para amostras dependentes e ANOVA com post-hoc de Tukey, adotando-se nível de significância de 5%. Os resultados demonstraram que a utilização de halteres com pesos de 2 e 4 kg, parece não afetar o desempenho dos idosos, principalmente do sexo masculino. Para o sexo feminino, detectou-se diferença significativa nas médias na segunda comparação realizada para o gênero. Todavia, essa diferença pode ter sido decorrente de fatores externos ao teste, visto que, as maiores médias obtidas foram para o RESISFOR "ajustado". Diante disso, busca-se facilitar ainda mais a avaliação da capacidade funcional da população idosa, sendo recomendada, para o RESISFOR, a utilização de halteres com peso de 2 Kg para mulheres e 4 kg para os homens, que são de baixo custo, fácil aquisição e acesso no comércio brasileiro.